The problem of diabetic hipoglycaemia - Derkacz, Marek; Chmiel-Perzyńska, Iwona; Nowakowski, Andrzej (Current Problems of Psychiatry, 2012)
The major goal in treating diabetes is the effective metabolic control of the disease as well as avoiding hypoglycaemia. Hypoglycaemia is an abnormally diminished content of glucose in the blood (below 55 mg/dl (3.0 m/M)) and an intrinsic element in every diabetic’s life. Diabetics experience hundreds or even thousands symptomatic and asymptomatic hypoglycaemic episodes throughout their lives. Acute hypoglycaemic episodes may lead to convulsions, coma or even death. They increase the risk of trauma resulting from those episodes. Recurrent acute hypoglycaemic episodes may lead to changes in behaviour as well as cause the worsening of cognitive functions. Episodes of hypoglycaemia occur more often in people suffering from diabetes type 1, however the frequency of those episodes significantly increases with the duration of diabetes type 2 and the risk of occurrence of those episodes approaches the risk present in diabetes type 1. The occurrence of hypoglycaemia worsen the quality of patient’s life. The problem of hypoglycaemia in diabetes particularly concerns children, their parents and elderly people. The consequence of recurrent hypoglycaemia is more frequent occurrence of depression and anxiety symptoms. Hypoglycaemia is also one of the main factors limiting the correct control of glycaemia in patients. Striving to achieve glycaemic targets should be individualised in many cases. Moderating the criteria of balancing carbohydrate metabolism in the case of elderly people may not be efficient to prevent hypoglycaemic incidents. An additional proceeding to effectively limit the risk of hypoglycaemic incidents among patients is educational activity.